PENERAPAN TEKNOLOGI UNTUK MENGURANGI EMISI GAS RUMAH KACA - Mohamad Sidik Boedoyo (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
Being located in the equator and also has bondaries with two tectonic plates, Indopnesia has various of energy resources, such as oil, coal, natural gas, as well as, renewable energy resources such as geothermal, solar, hydro, wind etc. In relation to the above mentioned conditions, Indonesia has a lot of potential to reduce greenhouse gas emmission through increasing the energy efficiency, fuel swiching, as well as utilization of CCS (carbon dioxide capture and storage) in the oil, gas and coal mining. Although Indonesia is not included in Kyoto Protocol’s country list, Annex I or Annex II, Indonesia is inclkuded among countries that had ratified the Earth Summit and the Kyoto Protocol. Therefore, it has a responsibility to help the developed country reduce their greenhouse gas emmission through application of environmental friendly technologies in the framework of Clean Development Mechanism.